Design and In Situ Growth of Cu2O‐Blended Heterojunction Directed by Energy‐Band Engineering: Toward High Photoelectrochemical Performance. Issue 12 (23rd February 2022) - Zheng, Lingcheng; Diao, Lingxue; Zhang, Rui; Sun, Xingjun; Lv, Qiaoya; Chen, Feifei; Li, Yan; Liu, Hui; Zhang, Xinghua; Lu, Zunming; Wang, Weihua; Lu, Feng; et al.
Abstract: In the field of photoelectrochemical (PEC) water splitting, cuprous oxide (Cu2 O) is one of the most promising photocathode materials, but its performance is restricted by poor carrier separation ability and low photovoltage. In order to overcome these limitations, a new kind of Cu2 O‐ZnO blended heterojunction photocathode is designed and prepared by novel one‐step thermal oxidation method. ZnO granules are uniformly distributed in Cu2 O film matrix, forming a granular structure, which enhances the band bending of Cu2 O in the electrolyte and improves the photovoltage. In addition, the formed ladder type band alignment of Cu2 O‐ZnO facilitates the spatial separation of photoexcited carriers. Different from the conventional layered heterojunction, the granular structured heterojunction proposed in this work extends the built‐in electric field region and further promotes the transmission of photoexcited carriers from the photoelectrode to the electrolyte. At 0 V vs reversible hydrogen electrode (RHE), the photocurrent density of Cu2 O‐ZnO film is as high as −8.7 mA cm −2, which is over 6 times that of bare Cu2 O (−1.3 mA cm −2 ). The onset potential positively shifts from 0.57 V vs RHE to 0.78 V vs RHE. This work provides an effective strategy for improving the PEC performance from the perspective of band alignment and material structure. Abstract : This work provides a blended heterojunction structure and in‐situ growth method of Cu2 O‐ZnO film. Benefiting from the energy‐band modulating, the ZnO paricles improve the photovoltage, separate the photo‐carriers and hinder the photocorrosion of Cu2 O. As a result, the photocurrent density of Cu2 O‐ZnO photocathode is as high as −8.7 mA cm 2, the onset potential positively shifts to 0.78 V vs reversible hydrogen electrode and the attenuation of photocurrent is also inhibited.